2011
DOI: 10.1016/j.bpj.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific Transcription-Factor-DNA Binding Influences Nucleosome Occupancy in Yeast

Abstract: Quantitative understanding of the principles regulating nucleosome occupancy on a genome-wide level is a central issue in eukaryotic genomics. Here, we address this question using budding yeast, Saccharomyces cerevisiae, as a model organism. We perform a genome-wide computational analysis of the nonspecific transcription factor (TF)-DNA binding free-energy landscape and compare this landscape with experimentally determined nucleosome-binding preferences. We show that DNA regions with enhanced nonspecific TF-DN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 48 publications
11
36
0
Order By: Relevance
“…We thus investigated the sequence context effect on RNAP pausing between the true and false PIEs. As described below and in our previous studies (24)(25)(26)(27)(28)(29), we have previously revealed that nonconsensus repetitive DNA sequence elements in the vicinity of a consensus protein-binding motif statistically enhance the protein binding to its "site." This finding led us to hypothesize that a similar context effect could provide the mechanism responsible for the genome-wide regulation of RNAP pausing at PIE motifs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We thus investigated the sequence context effect on RNAP pausing between the true and false PIEs. As described below and in our previous studies (24)(25)(26)(27)(28)(29), we have previously revealed that nonconsensus repetitive DNA sequence elements in the vicinity of a consensus protein-binding motif statistically enhance the protein binding to its "site." This finding led us to hypothesize that a similar context effect could provide the mechanism responsible for the genome-wide regulation of RNAP pausing at PIE motifs.…”
Section: Resultsmentioning
confidence: 99%
“…We have characterized the mechanism of this context effect (24)(25)(26)(27)(28)(29) as an extension of the concept for nonspecific protein-DNA binding introduced by von Hippel and coworkers (30)(31)(32)(33) 40 y ago. Briefly, nonspecific protein-DNA binding (i.e., protein sliding on DNA) represents an electrostatically dominated mechanism, and it was usually assumed that it is uniform (on average) and entirely nonspecific outside of short specific recognition motifs along the genomic DNA (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our theoretical calculations make surprising predictions that the sequence heterogeneity almost always lead to faster protein search for targets on DNA despite the fact that it lowers the effective protein-DNA binding affinity. [43][44][45][46] And the stronger the contribution of the 1D search modes, the more relevant will be the effect of sequence heterogeneity.…”
Section: Sequence Heterogeneitymentioning
confidence: 99%
“…First, gene promoters are known to serve as center points, relative to which the nucleosomes are positioned (Mavrich et al 2008a; Afek et al 2011). However, nucleosome-free regions (NFRs) are also well defined in yeast, which appear to lack ubiquitous promoter-proximal pausing (Rhee and Pugh, 2012), indicating that it is not pausing, but the promoter itself that may be responsible for establishing the NFR.…”
Section: Parting the Chromatin: Friend Or Foe?mentioning
confidence: 99%